Arylboration of Enecarbamates for the Synthesis of Borylated Saturated N‐Heterocycles. Issue 46 (17th October 2022) - Trammel, Grace L.; Kannangara, Prashansa B.; Vasko, Dmytro; Datsenko, Oleksandr; Mykhailiuk, Pavel; Brown, M. Kevin
Abstract: Two catalytic systems have been developed for the arylboration of endocyclic enecarbamates to deliver synthetically versatile borylated saturated N‐heterocycles in good regio‐ and diastereoselectivities. A Cu/Pd dual catalytic reaction enables the synthesis of borylated, α‐arylated azetidines, while a Ni‐catalysed arylboration reaction efficiently functionalizes 5‐, 6‐, and 7‐membered enecarbamates. In the case of the Cu/Pd‐system, a remarkable additive effect was identified that allowed for broader scope. The products are synthetically useful, as demonstrated by manipulations of the boronic ester to access biologically active compounds. Abstract : Saturated N‐heterocycles are important motifs found in many biologically active molecules. In this work, difunctionalization of 4–7‐membered enecarbamates is achieved using both Cu/Pd and Ni‐catalysed arylboration to deliver synthetically versatile borylated saturated N‐heterocycles in good selectivity. The products are synthetically useful, as demonstrated by manipulations of the boronic ester to access biologically active compounds.